Economic impact of closer cross-strait economic relations on taiwan : a general equilibrium analysis. - Chua, Hui Mien. (2008)
In this paper, we explore the economic impact on Taiwan when it removes trade barriers with China using a Computable General Equilibrium (CGE) model, based on ORANI. Simulated results generally reveal a favourable position for Taiwan.